Financial crises: Lessons from the Nordic experience - Honkapohja, Seppo (Journal of Financial Stability, 2014)
The current financial crisis is the 19th such crisis in the post-war period in advanced economies. Recent literature classifies the Nordic crises in Norway, Sweden and Finland in late 1980s and early 1990s among the Big Five crises that have happened before the current crisis, which is now of a global nature. This paper outlines the developments of the Nordic crises, reasons behind them and crisis management by the authorities. Relatively more emphasis is placed on the Finnish crisis, as it was the deepest one. The paper concludes by considering the lessons that can be drawn from the Nordic crises.